DOXYCYCLINE PHOTOCATALYTIC DEGRADATION USING MESOPOROUS CARBON NITRIDE (MCN) UNDER VISIBLE LIGHT - Azzahra Hanggararas Sasdika; Ervin Nurhayati; Isni Arliyani; Muchammad Tamyiz; Adhi Yuniarto; Yu Syuan Liou; Checia Hu (Purifikasi, 2026)
Antibiotic contamination in aquatic environments has become a global concern due to its potential contribution to antimicrobial resistance and adverse impacts on aquatic ecosystems. Photocatalysis using carbon nitride-based semiconductor materials has emerged as a promising approach for the removal of antibiotic pollutants. This study aimed to evaluate the performance of Mesoporous Carbon Nitride (MCN) for the degradation of DOX under visible-light irradiation at initial concentrations of 0.5, 5, 20, and 50 mg/L. Photocatalytic experiments were conducted in a laboratory-scale reactor equipped with a magnetic stirrer to maintain solution homogeneity. DOX concentration was determined using UV–Vis spectrophotometry, while ammonia (NH₃-N) analyses were performed to investigate compound transformation during the degradation process. The results demonstrated that both irradiation time and initial DOX concentration significantly influenced the degradation performance. The highest degradation efficiency was achieved at an initial concentration of 50 mg/L, reaching 36.51% after 150 min of visible-light irradiation, whereas the degradation efficiency at 20 mg/L was 12.29%. Degradation rate analysis revealed maximum values of 0.103 mg L⁻¹ min⁻¹ and 0.514 mg min⁻¹ g⁻¹ at 50 mg/L. Changes in ammonia concentration indicated that the photocatalytic process not only promoted DOX degradation but also facilitated the transformation of nitrogen-containing compounds during the reaction. Meanwhile, the apparent negative degradation efficiencies observed at 0.5 and 5 mg/L were attributed to analytical limitations associated with UV–Vis measurements at low concentrations. These findings demonstrate the potential of MCN as a visible-light-responsive photocatalyst for the treatment of antibiotic-contaminated wastewater.